Nigeria : report by Sir F. Lugard on the amalgamation of Northern and Southern Nigeria - Lugard, Frederick John Dealtry 1858-1945 (Adam Matthew Digital, 1919)
Colonial Office file containing a report by the High Commissioner of Northern Nigeria, outlining the social and political conditions in Nigeria, the colonial administrative structures and the role and responsibilities of the British administration